2016
DOI: 10.1161/atvbaha.116.307481
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine Meets microRNA

Abstract: Cardiovascular disease accounts for almost half of all deaths worldwide, and has now surpassed infectious disease as the leading cause of death and disability in developing countries. At present, therapies such as LDL-lowering statins and anti-hypertensive drugs have begun to bend the morality curve for coronary artery disease (CAD); yet, as we come to appreciate the more complex pathophysiological processes in the vessel wall, there is an opportunity to fine-tune therapies to more directly target mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…The understanding of these effects of miRNAs on the specific pathways that lead to atherosclerosis of a vessel, may allow for the development of miRNA based biologic therapy against cardiovascular disease. So far, current miRNA therapy focuses on systemic administration of either anti-miRNA delivery, to decrease the levels of certain microRNAs, or the introduction of synthetic miRNAs, known as miRNA mimics, that are used to increase the levels of those miRNAs which are seen to be down-regulated in some diseases131. For instance, the introduction of miR-126, which is highly concentrated within ECs, has been shown to be enhance the expression of endothelial growth factors and hence is believed to have the potential of being used to stimulate endothelial repair129.…”
Section: Mirnas In Smc Differentiationmentioning
confidence: 99%
“…The understanding of these effects of miRNAs on the specific pathways that lead to atherosclerosis of a vessel, may allow for the development of miRNA based biologic therapy against cardiovascular disease. So far, current miRNA therapy focuses on systemic administration of either anti-miRNA delivery, to decrease the levels of certain microRNAs, or the introduction of synthetic miRNAs, known as miRNA mimics, that are used to increase the levels of those miRNAs which are seen to be down-regulated in some diseases131. For instance, the introduction of miR-126, which is highly concentrated within ECs, has been shown to be enhance the expression of endothelial growth factors and hence is believed to have the potential of being used to stimulate endothelial repair129.…”
Section: Mirnas In Smc Differentiationmentioning
confidence: 99%
“…30 Studies reported in ATVB emphasize the diversity of miRNA species that affect different pathways underlying atherogenesis and vascular biology. For instance, Ouimet et al 31 investigated whether miR-33 contributes to cholesterol homeostasis by targeting autophagy.…”
Section: Micro-rnas As Biomarkers and Therapeutic Targets In Atheroscmentioning
confidence: 99%
“…52 Despite the importance of the above miRNAs in atherosclerosis, therapeutic modulation in a context-specific manner remains elusive. Gadde and Rayner 30 reviewed the emergence of miRNA-based therapies as potential therapies for atherosclerosis in coronary arteries and other vascular beds by targeting specific causal pathways. The review also introduced the concept of nanoparticle development as a platform to specifically target the vessel wall.…”
Section: Dron Et Al Recent Genetic Highlights Of Atvb E161mentioning
confidence: 99%
“…After the miRNAs are loaded onto the NPs, an intravenous route of administration 18 would be the least invasive option. Different therapeutic candidate miRNAs have been described,3, 19, 20, 21, 22 and different NPs for miRNA delivery are now being explored as potential treatments for cardiovascular pathologies—namely, viral,23, 24, 25, 26, 27, 28, 29, 30 lipid,31, 32, 33, 34 and polymer-based35, 36, 37 platforms.…”
Section: Introductionmentioning
confidence: 99%